Comparison of Effectiveness of Methotrexate Monotherapy with Combination Therapy in The Patients with Rheumatoid Arthritis - Ümit Dündar; Deniz Evcik; Aycan Türel; Vural Kavuncu (Archives of Rheumatology, 2006)
Objective: Substantial changes occurred in the treatment of rheumatoid arthritis (RA) after the mid 1990s. Disease modifying antirheumatic drugs (DMARD) were started earlier in the course of the disease with higher doses and combination as well as anti-cytokine therapies were preferred in the treatment of RA. The aim of this study was to compare effectiveness of methotrexate with combination therapy (methotrexate + other DMARD) in the patients with RA. Patients and Methods: Retrospectively 40 patients with a diagnosis of RA (according to American College of Rheumatology criteria) and at least one year of follow up, enrolled in this study. A total of 17 patients in the first group took methotrexate monotherapy for a year. There were 23 patients in the combination therapy group and they took combination therapy with two drugs (methotrexate + other DMARD) for a year. Patients were evaluated for clinical, and laboratory parameters at the beginning and after one year. Clinical parameters included number of swollen joints, number of tender joints and disease activity score (DAS) 28). Laboratory evaluation included erythrocyte sedimentation rate and C-reactive protein measurements. Results: DAS 28 score was 3.1 ± 1.3 at the beginning and 2.85 ± 1.1 after one year in the methotrexate group. DAS 28 score in combination therapy group was; 4.4 ± 1.4 at the beginning and 2.88 ± 1.1 after one year. DAS 28 score was significantly higher in combination therapy group than in methotrexate group at the beginning. But, after one year of therapy, DAS 28 scores were similar in both group. The change in DAS 28 scores after one year of therapy was significantly higher in combination therapy group. Conclusion: This study shows that combination therapy controls disease activity more successfully in the patients with RA when compared with methotrexate monotherapy. (Rheumatism 2006; 21: 56-9)